Political autobiographies and memoirs in antiquity : a Brill companion - Marasco, Gabriele. (Brill's Companions to Classical Studies., 2011)
Ancient autobiography has been the object of several studies and meetings. However, these have focused chiefly on the philosophical and literary aspects. This book aims to examine the development of political autobiography and memoirs in the Greek and Roman world, stressing, instead, the relation of a single work with the traditions of the genre and also the influence of the respective aims of the authors on the composition of autobiographies. At times these works were written as a means of propaganda in a political struggle, or to defend a past action, and often to furnish material to historians. Nonetheless, they still preserve the personal viewpoint and voice of the protagonists in all their vividness, even if distorted by the aim of defending their record. Political Autobiographies and Memoirs in Antiquity will be a highly valuable and useful reference tool for both scholars and students of Greek and Roman history and literature.